Systemic chemotherapy decreases brain glucose metabolism. (1st October 2014) - Horky, Laura L.; Gerbaudo, Victor H.; Zaitsev, Alexander; Plesniak, Wen; Hainer, Jon; Govindarajulu, Usha; Kikinis, Ron; Dietrich, Jörg
Abstract Objective Cancer patients may experience neurologic adverse effects, such as alterations in neurocognitive function, as a consequence of chemotherapy. The mechanisms underlying such neurotoxic syndromes remain poorly understood. We here describe the temporal and regional effects of systemically administered platinum‐based chemotherapy on glucose metabolism in the brain of cancer patients. Methods Using sequential FDG‐PET/CT imaging prior to and after administration of chemotherapy, we retrospectively characterized the effects of intravenously administered chemotherapy on brain glucose metabolism in a total of 24 brain regions in a homogenous cohort of 10 patients with newly diagnosed non‐small‐cell lung cancer. Results Significant alterations of glucose metabolism were found in response to chemotherapy in all gray matter structures, including cortical structures, deep nuclei, hippocampi, and cerebellum. Metabolic changes were also notable in frontotemporal white matter (WM) network systems, including the corpus callosum, subcortical, and periventricular WM tracts. Interpretation Our data demonstrate a decrease in glucose metabolism in both gray and white matter structures associated with chemotherapy. Among the affected regions are those relevant to the maintenance of brain plasticity and global neurologic function. This study potentially offers novel insights into the spatial and temporal effects of systemic chemotherapy on brain metabolism in cancer patients.